2020
DOI: 10.18016/ksutarimdoga.vi.533723
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Dripper Properties on Entomopathogenic Nematode Application in Drip Irrigation

Abstract: There are many types of drippers with different flow path length, flow path shape and filtration surface. EPN delivery performance of the most commonly used four different types of drippers (in-line short path, in-line long path, in-line cylindrical and on-line button) was examined with a drip irrigation system in laboratory conditions. Under four different pressures (0.5, 1, 1.5, 2 bar), EPNs were applied to 1-liter beakers with irrigation system and discharged nematodes were counted under a stereomicroscope.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In another set of studies, pressure and nozzle types suitable for EPN application were researched, and the appropriate nozzle types were determined (Brusselman et al, 2011(Brusselman et al, , 2012b. Furthermore, Erdoğan et al (2020) investigated suitable dripper types for EPNs and found a significant difference in application success among different drippers, in parallel with this study. These studies showed that the efficacy of EPNs can be increased during and after application.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In another set of studies, pressure and nozzle types suitable for EPN application were researched, and the appropriate nozzle types were determined (Brusselman et al, 2011(Brusselman et al, , 2012b. Furthermore, Erdoğan et al (2020) investigated suitable dripper types for EPNs and found a significant difference in application success among different drippers, in parallel with this study. These studies showed that the efficacy of EPNs can be increased during and after application.…”
Section: Discussionmentioning
confidence: 83%
“…Many studies have been conducted on the application of EPNs in drip irrigation (Curran and Patel, 1988;Reding et al, 2004;Arrington et al, 2016). However, few studies have examined the effects of drippers on EPN application (Erdoğan et al, 2020). In fact, we believe that in some studies comparing EPN efficacy with chemical pesticides, EPNs failed due to unsuitable dripper selection (Arrington et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations